PUSAT PERBELANJAAN MODERN DI KECAMATAN PONTIANAK BARAT (JMARS: Jurnal Mosaik Arsitektur, 2021)
The increase in population and economic development in Pontianak City has increased every year, and it is also in one of the districts in Pontianak City, namely West Pontianak District, which has a fairly high level of trade and services. To follow up on this, we need a container or Modern Shopping Center in West Pontianak District by providing open spaces or (open malls) so that it can accommodate consumer needs as well as enjoy open spaces. There are secondary data that provide discussion of malls, mall classification, and theories related to modern centers. The Modern Shopping Center in West Pontianak District provides an attractive design by providing a solid facade with two masses of buildings served by a sky bridge. This Modern Shopping Center in West Pontianak District is located in a trade and service location. The design method is a systematic stage, the design method used is the J.C Jones method in the Architectural Design Methods book. The stages used are the stages of ideas, information, analysis, synthesis, evaluation, and optimization. The purpose of the design is to produce a design for a Modern Shopping Center in West Pontianak District, which is able to accommodate the community in West Pontianak District by providing recreational and entertainment areas with the concept of Open Mall and providing spaces for mall visitors such as clothing and accessories retail, culinary retail, educational retail, toy retail, plant retail, sports retail, indoor activities, and outdoor activities and other supporting functions.